Pengaruh Penatausahaan Aset Tetap, Sistem Pengendalian Internal, dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan di Kota Palembang - Fitrania, Nadysa Aulia; Martini, Rita; Dwitayanti, Yevi (P3M Politeknik Negeri Banjarmasin, 2022)
The purpose of this study was to analyze the impact of fixed asset administration, internal control systems, and human resource competencies on the quality of financial statements in Palembang city. The research data came from questionnaires distributed to 51 OPDs in Palembang City with a total sample of 102 respondents using probability sampling technique. The data were processed with narrative statistics and multiple linear regression analysis through SPSS software. The results showed that partially the administration of fixed assets had no effect on the quality of Palembang City's financial statements, the internal control system had an effect on the quality of Palembang City's financial statements, while human resource competence had no effect on the quality of Palembang City's financial statements. As for the simultaneous analysis, asset administration, internal control systems, and human resource competencies affect the quality of Palembang City Government financial statements with an adjusted R square value of 0.283.